Behavioral, Environmental, and Socioeconomic Determinants of Chronic Obstructive Pulmonary Disease in a Rural Agricultural Setting: A Case-Control Study in Suphan Buri, Thailand - Phuphaniat, Marut; Jeefoo, Phaisarn; Paengwangthong, Wipop; Lerk-U-Suke, Sawarin (National Journal of Community Medicine, 2026)
Background: COPD poses a growing public health burden in Thailand, yet combined personal, behavioral, socioeconomic, and environmental determinants remain insufficiently characterized in agricultural communities. This study conducted to quantify independent factors associated with COPD occurrence among adults in Suphan Buri Province, Thailand. Methods: A matched case-control study enrolled 114 newly diagnosed COPD cases and 228 frequency-matched controls (1:2 ratio) from district hospitals and community health centers during June-August 2025. COPD was confirmed by post-bronchodilator spirometry (FEV₁/FVC <0.70). A validated structured questionnaire assessed socioeconomic, behavioral, and environmental exposures. Binary logistic regression estimated adjusted odds ratios (aOR) with 95% confidence intervals. Results: Asthma history showed the strongest association (aOR=9.74; 95%CI: 3.04-31.17), followed by heavy smoking (Brinkman Index ≥400; aOR=5.26), frequent workplace dust/smoke exposure (aOR=4.41), household smoker presence (aOR=4.01), agricultural burning (aOR=3.08), workplace smoking exposure (aOR=2.21), vehicle exhaust (aOR=2.47), and proximity to main roads (aOR=2.26). Higher monthly income was protective (aOR=0.47). Model discrimination was robust (AUC=0.843; overall accuracy=81.3%). Conclusion: COPD risk in this agricultural population reflects multidomain determinants. Integrated prevention strategies targeting tobacco control, air pollution, socioeconomically vulnerable groups are warranted.